Totality, Charisma, Authority : The Origins and Transformations of Totalist Movements - Murariu, Mihai (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
This interdisciplinary endeavour portrays the central features of militant movements which hold totality as an important part of their doctrinal core. Revisiting the importance of modernity, utopianism, eschatology, charisma, psychology and the history of ideas, Mihai Murariu pursues a reconstruction of the historical requirements for the emergence of such movements. Making a central use of the concept of totalism, the work establishes a conceptual bridge from antiquity to the contemporary period, whilst also arguing for the suitability of the term in comparison to totalitarianism or political religion. The author also proposes a distinct taxonomy for structural elements, variants, and development phases which may be encountered in totalist movements. Contents - Totality and Totalism: Theory and Concepts - Evolving Perspectives: Eschatology and Utopia - The Totalist Types: Between Renovative and Utopian Strands - Totalism Transformed: Power, Purity, and Truth from Heterodoxy to Ideocracy - The Legion of the Archangel Michael and the "Hybrid" Totalist Type Target Groups - Lecturers and students of political science, security studies, history, sociology, philosophy - Academics, policymakers About the Author Mihai Murariu is an independent researcher, as well as a writer and essayist. His research interests focus on the roots of radicalism, modernity, terrorism, and the interplay between ideology, security and militant movements, and the challenges these bring about in contemporary pluralist societies.
Keywords: Social sciences.; Political theory.; elektronické knihy; electronic books